Comprehensive Analysis of Abortion: Risk Factors, and Management in Reproductive Health - Musyarof, Disa Fadil; Zahira, Lu’lu Al Fatina; Rifa’i, Ahmad Nur; Iqlima, Aisya Yafis; Aziri, Zirly Vera; Putra, Anak Agung Gede Agung Difa Agusta Pramana; Mujahid, Sabila Izzatina Azmy; Zulkarnaen, Decky Aditya (Jurnal Biologi Tropis, 2024)
Abortion is defined as the process of expelling the products of conception before the fetus is fit to survive. The fetus is said to be viable or able to survive when it reaches 20 weeks of pregnancy or weighs 500 grams. The purpose of this article is to provide a comprehensive understanding of abortion, including definition, epidemiology, etiology, risk factors, classification, and management of abortion. The method used is a literature review that includes various academic sources and the latest research related to abortion. Based on the type of occurrence, abortion is divided into two, namely spontaneous abortion and intentional abortion.. Based on the type of event, abortion is divided into two, namely spontaneous abortion and intentional abortion. Intentional abortion is divided into abortion provokatus medicinalis or abortion carried out with medical indications and abortion provokatus criminalis, namely abortion without a valid medical reason. Meanwhile, based on the clinical picture, abortion is divided into several types, namely imminens abortion, incipient abortion, incomplete abortion, complete abortion, missed abortion, and septic abortion. The various types of abortion have their own management.